وحدة الوجود عند صدر الدين الشيرازي وأبن عربي (Journal of Imam Al-Kadhim College, 2023)
The Unity of Existence is a philosophical doctrine that says that God and nature are one reality, and that God is the real existence, and they consider God the image of this created world. It has proof in the travels, and it is what he said in his book, The Transcendental Wisdom: ((The simple truth is all things)) and the people of mysticism and philosophy followed him, including Sayyid Muhammad Husayn al-Tabatabai and Sayyid Ali al-Qadi, his teacher (may God have mercy on them both)There is still debate about the issue of (unity of existence) between theologians and philosophers. Some of them believe that it is true, and some of them infer its invalidity. In any case, one should not delve into these philosophical issues except after studying the science of theology and understanding the doctrinal structures through the Book and the Sunnah, just as This is confirmed by most scholars and jurists.
Keywords: الكلمات المفتاحية: وحدة الوجود، الالوهية، ابن عربي، الملا صدر الشيرازي